2022
DOI: 10.1155/2022/4632823
|View full text |Cite|
|
Sign up to set email alerts
|

Left Atrial Appendage Depth and Tachycardia Bradycardia Syndrome as Important Predictors of Left Atrial Appendage Thrombus in Patients with Nonvalvular Atrial Fibrillation

Abstract: Background. Atrial fibrillation (AF) is the most common heart rhythm disorder that has been shown to be associated with a significant increase in stroke and systemic embolism risk. The left atrial appendage (LAA) is a finger-like extension originating from the left atrium; the formation of thrombus in LAA is the main reason of stroke and systemic embolism in patients with nonvalvular atrial fibrillation (NVAF). This study is aimed at finding out the risk of left atrial appendage thrombus (LAAT) in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…The C-statistics of it for ischemic stroke only ranged from 0.57 to 0.67 across multiple cohorts ( 37 ). In some of these cases, the relatively higher AUC was obtained from a high specificity at the cost of sensitivity, which drops to 10.80% ( 38 ).…”
Section: Risk Assessment Of Thrombosis In Patients With Af: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The C-statistics of it for ischemic stroke only ranged from 0.57 to 0.67 across multiple cohorts ( 37 ). In some of these cases, the relatively higher AUC was obtained from a high specificity at the cost of sensitivity, which drops to 10.80% ( 38 ).…”
Section: Risk Assessment Of Thrombosis In Patients With Af: ...mentioning
confidence: 99%
“…Left atrial appendage depth (LAAD) was found to be related to thrombus risk with an OR of 4.216. Its predictive value is considerable, having an AUC of 0.735, with a sensitivity of 75.7% and a specificity of 74.9%, and the cutoff point was more than 23.45 mm ( 38 ). An LAA end-systolic volume and an end-diastolic volume larger than 18.45 and 9.49 mL were believed to be critical values ( 47 ).…”
Section: Summary Of Commonly Used Morphological and Hemodynamic Index...mentioning
confidence: 99%
“…Анатомические 23,45 мм (ОР 4,216, 95% ДИ: 1,869-9,510, P=0,001) и площадь уЛП, величина которой обратно пропорциональна скорости кровотока в уЛП (β=-0,185, P=0,033) [27,108].…”
Section: ____________________________________________________________...unclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ] This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1] This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%